Vitamin D and Susceptibility of Chronic Lung Diseases: Role of Epigenetics - Sundar, Isaac K.; Rahman, Irfan (Frontiers in Pharmacology, 2011)
Vitamin D deficiency is linked to accelerated decline in lung function, increased inflammation, and reduced immunity in chronic lung diseases. Epidemiological studies have suggested that vitamin D insufficiency is associated with low lung function in susceptible subjects who are exposed to higher levels of environmental agents (airborne particulates). Recent studies have highlighted the role of vitamin D and vitamin D receptor (VDR) in regulation of several genes that are involved in inflammation, immunity, cellular proliferation, differentiation and apoptosis. Vitamin D has also been implicated in reversal of steroid resistance and airway remodeling, which are the hallmarks of chronic obstructive pulmonary disease (COPD) and severe asthma. VDR protein level is decreased in lungs of patients with COPD and VDR deficient mice. These mice develop an abnormal lung phenotype with characteristics of COPD, such as airspace enlargement and decline in lung function associated with increased lung inflammatory cellular influx, and immune-lymphoid aggregates formation. Dietary vitamin D may regulate epigenetic events, in particular on genes which are responsible for COPD susceptibility. Active metabolite of vitamin D, 1,25-dihydroxyvitamin D3 plays an essential role in cellular metabolism and differentiation via its nuclear receptor (VDR) that cooperates with several other chromatin modification enzymes (HATs, and HDACs), thus result in mediating complex epigenetic events in vitamin D signaling and metabolism. This review provides an update on the current knowledge and understanding on vitamin D, and susceptibility of chronic lung diseases in relation to the possible role of epigenetics in its molecular action. Understanding the molecular epigenetic mechanisms of vitamin D/VDR would provide rationale for dietary vitamin D-mediated intervention in prevention and management of chronic lung diseases linked with vitamin D deficiency.